PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA SATUAN POLISI PAMONG PRAJA KABUPATEN ENREKANG - Yustika, Sri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of work stress and work environment on employee performance in the Civil Service Police Unit, Enrekang Regency. The data collection techniques used in this study were observation, questionnaires, and documentation. The sample in this study amounted to 136 respondents. The data analysis technique in this study used multiple linear analysis techniques with the help of a computerized system (SPSS version 16 computer program). The results showed that work stress (X1) with the at-count value of 8.465 and at-table value of 1.65639 and a significance value of 0.000 <0.005. The results of the study partially work stress (X1) has a positive and significant effect on employee performance (Y). Work Environment Variable (X2) with a t value of 4.622 > 1.65639 and a significance value of 0.000 < 0.005. partially the work environment has a positive and significant effect on employee performance (Y).